Eye changes among HIV positive patients on antiretroviral therapy in Nepal - Labh, Rajan Kumar; Chaudhary, Meenu; Shah, Dev Narayan (Nepalese Journal of Ophthalmology, 2016)
Background: HIV/AIDS has various ocular manifestations. Objective: To find out eye findings among HIV positive patients in the era of antiretroviral therapy. Method This Hospital based cross sectional descriptive study was carried at B. P. Koirala Lions Centre for Ophthalmic Studies. Patient profile, WHO clinical stage, CD4+ cell count, duration of HIV, antiretroviral therapy, and systemic diseases were recorded. All the cases underwent ocular examination as per the study protocol and the findings were noted in a proforma developed for the study. The results were analysed with SPSS 14.0. Results: Of 100 HIV positive cases (including 55 antiretroviral therapy patients) 62% patients were male and 38% were female. The mean age of presentation was 27.72 years. Heterosexual transmission (62%) was the commonest mode of transmission of HIV. Thirty seven percent patients were illiterate. Systemic disease was present in 20% cases. Ocular complaint was present in 53% patients. Ocular disease was present in 40% HIV positive patients. Almost 55% of these cases were on antiretroviral therapy. Moderate to lower CD4 count patient had frequent eye disease. Patients in WHO Stage III and IV also had frequent eye problems. Anterior segment and external ocular disorder was present in 25% patients. The commonest manifestation was conjunctivitis in10% of total cases. Posterior segment manifestation was present in 11%, neuro-ophthalmic lesion in 4% and orbital lesion in 1% patient. Conclusion: Anterior segment manifestation is still common ocular manifestations in HIV positive patients in Nepal. Patients in WHO Stage III and IV are more vulnerable for eye changes. Young aged male and migrant workers are at risk of acquiring HIV in developing country like Nepal. Eye findings even in patientson antiretroviral therapy are similar. However, large sample size and long follow up study is required to have final disclosure. Nepal J Ophthalmol 2016; 8(15): 62-70